Oral rehabilitation and associated quality of life following mandibular reconstruction with free fibula flap: a cross-sectional study - Ritschl, Lucas M.; Singer, Hannes; Clasen, Franz-Carl; Haller, Bernhard; Fichter, Andreas M.; Deppe, Herbert; Wolff, Klaus-Dietrich; Weitz, Jochen (Frontiers in Oncology, 2024)
Introduction Mandibular reconstruction with the free fibula flap (FFF) has become a standardized procedure. The situation is different with oral rehabilitation, so the purpose of this study was to investigate the frequency of implant placement and prosthetic restoration. Additionally, the patients' situation, motivation, and treatment course were structurally assessed. Materials and methods All cases between January 2013 and December 2018 that underwent mandibular reconstruction in our department with a free fibula flap and gave written informed consent to participate were interviewed with two structured questionnaires about their restoration and quality of life. Additionally, medical records, general information, status of implants and therapy, and metric analyses of the inserted implants were performed. Results In total 59 patients were enrolled and analyzed in this monocentric study. Overall, oral rehabilitation was achieved in 23.7% at the time of investigation. In detail, implants were inserted in 37.3% of patients and showed an 83.3% survival of dental implants. Of these implanted patients, dental implants were successfully restored with a prosthetic restoration in 63.6. Within this subgroup, the satisfaction with the postoperative aesthetic and functional result was 79.9% and with the oral rehabilitation process was 68.2%. Satisfaction with the implant-borne prosthesis was 87.5%, with non-oral-squamous-cell-carcinoma patients being statistically significantly more content with the handling (p=0.046) and care (p=0.031) of the prosthesis. Discussion Despite the well-reconstructed bony structures, there is a need to increase the effort of achieving oral rehabilitation, especially looking at the patient’s persistent motivation for the procedure.